2014
DOI: 10.9790/3021-04270108
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Rays Absorption Studies of Garnet series of Gemstones at 1 Kev to 100 GeV: Theoretical Calculation

Abstract: -Mass attenuation coefficients and partial photon interactions have been calculated theoretically at incident photon energy 1 Kev to 100 GeV for garnet series of gemstones (Grosaularite (GS1), Pyrope(GS2), Spessarlite(GS3), Almandine(GS4), Uvarovite(GS5) and Androdite(GS6) using XCOM software [1]. The values of these parameters have been found to change significantly with incident photon energy and composition of the garnet series of gemstones. Half value layer (HVL) and tenth value layer (TVL) has also been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Its prop er ties suite a wide range of el e ments and compos ite ma te ri als from the Na tional In sti tute for Standards and Tech nol ogy NIST-XCOM da ta base. The lin ear at ten u a tion co ef fi cient mainly de pends on photon en ergy and the na ture of the sam ples such as chemi cal com po si tion and den sity [6][7][8][9][10][11][12]. In ad di tion, for most en vi ron men tal anal y ses, the value of the lin ear at ten u a tion co ef fi cient is not known and should be esti mated by mea sure ment or use of sam ples of as sumed com po si tion and den sity.…”
Section: Introductionmentioning
confidence: 99%
“…Its prop er ties suite a wide range of el e ments and compos ite ma te ri als from the Na tional In sti tute for Standards and Tech nol ogy NIST-XCOM da ta base. The lin ear at ten u a tion co ef fi cient mainly de pends on photon en ergy and the na ture of the sam ples such as chemi cal com po si tion and den sity [6][7][8][9][10][11][12]. In ad di tion, for most en vi ron men tal anal y ses, the value of the lin ear at ten u a tion co ef fi cient is not known and should be esti mated by mea sure ment or use of sam ples of as sumed com po si tion and den sity.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied linear and mass attenuation coefficients [13][14][15][16] for different energies and our research group [17][18][19][20]have studied interaction parameters for various low-Z composite materials. Also various researcher have studied gamma ray buildup factors of different types of materials such as amino acids, fatty acids and carbohydrates (21), polymers (22), Heavy metal oxide glass (23), which showed that the GP fitting is a very useful method for estimation of exposure and energy absorption build-up factors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when the gamma ray interacts with the material, the half-value layer (HVL), mean free path (MFP), effective atomic number (Z eff ), effective electron density (N el ), exposure buildup factors (EBF), and gamma ray energy absorption (EABF) are the fundamental quantities required to explain the penetration of nuclear radiation in matter. HVL, MFP, Z eff , N el , EBF, and EABF parameters can be computed utilizing the values of μ m [2]. Precise μ m values are wanted to provide fundamental results in many nuclear radiation fields like computerized tomography, radiation shielding, nuclear radiation dosimeter, fluorescence of gamma ray, and safety inspection [3].…”
Section: Introductionmentioning
confidence: 99%